2016
DOI: 10.1002/ehf2.12108
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function of patients with heart failure: facts and numbers

Abstract: Approximately 60% to 87% of patients with heart failure (HF) report sexual problems, and numbers as low as 31% of HF patients younger than 70 have normal sexual function. When compared with healthy elders, the amount of perceived sexual dysfunction might be similar (around 56%), but patients with HF are reporting more erectile dysfunction (ED) and also perceive that their HF symptoms (20%) or HF medication (10%) is the cause for their problems. The prevalence of ED is highly prevalent in men with cardiac disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…I have had the honour to be in the first HFA board lead by Prof. Brutsaert and since that time the HFA has grown stronger and been leading important developments in the field. For example, guidance documents that influence practice have been developed, facts and numbers that help us to form adequate research questions and curricula that help clinicians to deliver high quality care are made available. The nurse curriculum has been developed and was also updated .…”
Section: Our Questions To Tinymentioning
confidence: 99%
“…I have had the honour to be in the first HFA board lead by Prof. Brutsaert and since that time the HFA has grown stronger and been leading important developments in the field. For example, guidance documents that influence practice have been developed, facts and numbers that help us to form adequate research questions and curricula that help clinicians to deliver high quality care are made available. The nurse curriculum has been developed and was also updated .…”
Section: Our Questions To Tinymentioning
confidence: 99%
“…As only one of the studies dealt with sexual self-efficacy, it was not possible to draw any definite conclusions regarding the relationship between sexual self-efficacy and depression. This issue needs urgent further exploration, as sexual dysfunction has been reported in 60% -87% of the patients with HF [65]. Furthermore, reliance upon the BDI [50], which includes a number of symptoms (e.g., sexual incompetence and fatigue) common to both HF and depression, may have contributed to inaccuracies regarding the measurement of depression.…”
Section: Sexual Behaviourmentioning
confidence: 99%
“…13 Newer research has shown that oncometabolites, secreted by tumours, can also cause cardiovascular dysfunction independent of cardiotoxic effects of anti-cancer treatments, 14,15 but much more research is needed is this area. So far, a lot of research has focused on anaemia, 40 52,53 Newer research in heart failure and cancer also focuses on the understanding and more importantly, on how to treat anorexia, 54,55 cachexia, 56,57 and sarcopenia. 18-20 Vice versa it is currently unclear whether heart failure itself can cause cancer.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a lot of research has focused on anaemia, 40,41 iron deficiency, 42,43 kidney disease, 44,45 chronic obstructive pulmonary disease, 46,47 sleep apnoea, 48,49 liver dysfunction, 50,51 and sexual dysfunction. 52,53 Newer research in heart failure and cancer also focuses on the understanding and more importantly, on how to treat anorexia, 54,55 cachexia, 56,57 and sarcopenia. 58,59 These rather new areas of research are a common problem in chronic diseases, gaining growing attention from the scientific community.…”
Section: Introductionmentioning
confidence: 99%